IMPLEMENTASI MODEL PEMBELAJARAN VARK-FLEMING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI GELOMBANG MEKANIK - Muhamad Lutfi Alfazri; Rahmat Rizal; Ernita Susanti (Journal of Teaching and Learning Physics, 2026)
This study aims to address the low cognitive learning outcomes of students at one of the state high schools in Tasikmalaya, by implementing the Visual, Auditory, Read/Write, Kinesthetic (VARK-Fleming) learning model to enhance students' cognitive learning outcomes in the topic of Mechanical Waves. This research is classified as quantitative, using a non-equivalent control group design. The population consists of the XI MIPA class at SMA Negeri 3 Tasikmalaya, with XI MIPA 4 as the experimental class and XI MIPA 5 as the control class. The assessment instrument comprises 10 essay questions covering 4 indicators of cognitive learning outcomes: C1, C2, C3, and C4. Data analysis techniques involve t-tests and N-gain values, with results indicating that  > , specifically 6.44 > 2.35, and an N-gain value of 0.82, which is categorized as high. It can be concluded that implementing the Visual, Auditory, Read/Write, Kinesthetic (VARK-Fleming) learning model can improve students' cognitive learning outcomes on the topic of mechanical waves and also assist teachers in designing lessons that consider students' learning style preferences.